2017
DOI: 10.1177/1071100717704941
|View full text |Cite
|
Sign up to set email alerts
|

Hallux Valgus Correction Comparing Percutaneous Chevron/Akin (PECA) and Open Scarf/Akin Osteotomies

Abstract: Both groups showed comparable good to excellent clinical and radiologic outcomes at final follow-up. However, the PECA group had significantly less pain in the first 6 weeks following surgery. Level of Evidence Level II, prospective comparative study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
152
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(171 citation statements)
references
References 38 publications
11
152
2
4
Order By: Relevance
“…Uma possível complicação encontrada na queilectomia pela técnica cirúrgica percutânea é a lesão do nervo cutâneo dorsomedial, podendo ser encontrado em até 15% dos casos, segundo um estudo realizado em cadáveres (23) . Entretanto, no presente estudo, não foram observados sinais de hipoestesia em nenhum caso operado.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Uma possível complicação encontrada na queilectomia pela técnica cirúrgica percutânea é a lesão do nervo cutâneo dorsomedial, podendo ser encontrado em até 15% dos casos, segundo um estudo realizado em cadáveres (23) . Entretanto, no presente estudo, não foram observados sinais de hipoestesia em nenhum caso operado.…”
Section: Discussionunclassified
“…Ainda não existem trabalhos comparando o nível de dor pós-operatória nos pacientes submetidos à cirurgia aberta ou percutânea para hálux rígido, porém o trabalho prospectivo randomizado publicado por Lee et al (23) , demonstrou uma signifitiva redução da dor pós-operatória nos casos abordados de hálux valgo pelo Chevron percutâneo, em relação ao Scarf.…”
Section: Discussionunclassified
“…One study was excluded because it's retrospective article and one for the format of continuous variables outcome were not mean±SD.Therefore, five studies matched the selection criteria and were suitable for meta-analysis. [9][10][11][12][13] They are all randomized control trials (Figure 1 osteotomy could achieved better HVA degree compared Scarf osteotomy,but in some researches the results showed that scarf osteotomy was expected to correct moderate and severe hallux valgus better than chevron osteotomy. 14,15 Because in our study only two articles described different severity of the hallux valgus deformity,and one investigator divided the group into three subgroups base on the severity of hallux valgus,so we haven't evaluated the difference in moderate and severe hallux valgus,but we thought the classification of hallux valgus is necessary in the future researches which will indicate the effective of the different type of osteotomy procedures.…”
Section: Literature Searchmentioning
confidence: 99%
“…Forefoot MIS has experienced a vertiginous and sustained growth especially in the last decade. Clinical series and comparative studies have been published [47][48][49][50]. Additionally, cadaveric results [51,52], technique reports [53], and radiological validations [54,55] have been described.…”
Section: Current Situation and Indicationsmentioning
confidence: 99%
“…Additionally, cadaveric results [51,52], technique reports [53], and radiological validations [54,55] have been described. Despite the fact that for some authors percutaneous surgery of the forefoot lacks scientific support [56][57][58], recently two systematic reviews published support its indication in hallux valgus surgery [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Current Situation and Indicationsmentioning
confidence: 99%